American Investment Banking in the Context of Great Economic Crises - Hempel, Dominika (Studia Historiae Oeconomicae, 2017)
The bankruptcy of Lehman Brothers had a strong impact on the whole financial system and started the worst recession since the Great Depression. However, it was not the first crisis in the history of the USA. The purpose of this article is to present the history of investment banking during the main crises in the US history and their impact on the American economy. The article presents the following: a definition of investment banking, theoretical aspects of crises, changes in banking system regulations, and the history of the most important American investment banks, including the infamous Lehman Brothers.